Development of upper body strength training for pencak silat athletes in the adult competition category in pre-competition phase / Bahar Rozaq Maulidan, Kurniati Rahayuni and Muhammad Ihyauddin - Maulidan, Bahar Rozaq; Rahayuni, Kurniati; Ihyauddin, Muhammad (2024)
In pencak silat, upper body strength is very important to support the techniques performed, such as gripping, pulling, and counterattack techniques when we are knocked down by an opponent. So, a trainer must understand the training program that suits your needs. The aim of this development is to provide a variety of training tailored to the needs of Pencak silat athletes in the pre-competition phase. On this basis, researchers developed a strength training model based on the needs of the pencak silat sport by carrying out the Research and Development (R&D) method with an FGD (focus group discussion) approach with pencak silat experts and physical strength conditioning experts. The research was carried out in stages and resulted in 10 upper body strength training models in the pre-competition phase, namely (1) cobra push-up, (2) bench press, (3) barbell row, (4) bosu lateral step with battle rope, (5) one hand push combine, (6) multi planar pull with resistance band, (7) side pull with resistance band,(8) clean and press,(9) multi-directional pull for take down with resistance band,(10) from ground to up single hand pull push. This movement model has gone through expert testing and small and large group testing, so it is concluded that this product can be put into practice in training.